Źaṅ źuṅ sñan rgyud bla maʼi ñams rgyud rgyas pa skya smug gñis kyi gsuṅ pod : a collection of instructions incorporating the insights of the successive masters of the Źaṅ-źuṅ sñan-rgyud teachings of the Rdzogs-chen approach to Bon, together with other Rdzogs-chen instructions from the rediscoveries of Tshe-dbaṅ-rgyal-po - Tshe-dbaṅ-rgyal-po, Gter-ston (s.n.] ; distributor, Tibetan Bonpo Monastic Centre, 1973)
Dzogehen meditational precepts of Bonpo Lamaism.